Different Automatic Monitoring and Controlling Technique for Mushrooms - et. al., Mr. P.K .Angral, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Automation of mushroom farms can greatly reduce the human effort in maintaining suitable environment for mushroom growth by automatically controlling temperature, humidity and C02, thereby reducing overall cost and increases high production in mushroom yield. So it becomes very important to select the type of automation which suits to the farmer’s requirement and investment and ease of operation. This paper compares the various automation technologies that can be used in mushroom farming. This study should help the farmers to select the type of automation he can choose from the available automation technologies available around the world.